PHYTOCHEMICAL COMPOSITION OF CORIANDRUM SATIVUM L. (CO RIANDER) SEEDS AND ANTIBACTERIAL EFFECTS ON LAYING HENS - N. Ildz; A. Baldemir Klç; Y. Konca (Journal of Animal and Plant Sciences, 2018)
This study was performed to evaluate the antimicrobial activity of Coriandrum sativum L. (coriander) seed (CS) extracts and essential oil (EO) in vitro and in vivo assays. The major fatty acid was petroselinic acid ( 64%) and the main component of EO was linalool (82.2%). The petroleum ether extract (PE) had a higher antibacterial activity against Escherichia coli ATCC 25922, Staphylococcus aureus ATCC 25923, Klebsiella pneumoniae ATCC 700603 and Salmonella typhi NCTC 8394 compared to the methanol extract (ME). However, the ME extract was more effective against Enterococcus faecium NJ-1 ATCC than the PE extract. The PE extract increased the susceptibility of E. coli compared to other standard strains. The CS extracts and EO exhibited antimicrobial activity against standard strains of S. aureus, E. faecium, E. coli, K. pneumoniae and S. typhi. In vivo assays evaluated the effects of CS supplementation to diets on the antimicrobial activity in the intestines of laying hens. A total of 90 laying hens ( Hyline-5 White, 58 weeks old) were used and fed with diets supplemented with 0, 1, 2.5, 5 and 10% of seeds for 10 wk. The diet with Coriander seed decreased the ileal count of E. coli, S. aureus and E. faecium in hens significantly (p<0.01). In conclusion, CS was effective on standard bacteria (in vitro) and gastrointestinal microbiota (in vivo). Recently, plant essential oils (EOs) form a
Keywords: Coriandrum sativum; Laying hens; Fatty acid; Essential oil; Antibacterial activity; Apiaceae.